For love of the automobile : looking back into the history of our desires - Sachs, Wolfgang (Berkeley : University of California Press, 1992)
In his cultural analysis of the motor car in Germany, Wolfgang Sachs starts from the assumption that the automobile is more than a means of transportation and that its history cannot be understood merely as a triumphant march of technological innovation. Instead, Sachs examines the history of the automobile from the late 1880s until today for evidence on the nature of dreams and desires embedded in modern culture. Written in a lively style and illustrated by a.
Translation of: Die Liebe zum Automobil.
Includes bibliographical references (pages 223-227).
Print version record.
JSTOR
Keywords: Automobiles -- Social aspects -- History; Automobiles -- History; Technology and civilization; Automobiles -- Aspect social -- Histoire; Technologie et civilisation; SCIENCE -- Philosophy & Social Aspects; TECHNOLOGY & ENGINEERING -- Social Aspects; HISTORY -- Europe -- General; Automobiles; Automobiles -- Social aspects; Technology and civilization; Auto's.; Beeldvorming; Duitsland; History